Go luck yourself : 40 ways to stack the odds in your brand's favour - Nairn, Andy (Hampshire, Great Britain : Harriman House, 2021)
Luck is a four-letter-word in business circles. But, the truth is that fortune plays a part in every success story, and every failure. In Go Luck Yourself, one of the world's leading brand strategists explains how a hunting trip led to the invention of VELCRO®. How a little mermaid inspired a famous campaign for Amazon. How a stolen rabbit spurred on Walt Disney. And, more importantly, how you can stack the odds in your brand's favor.
Intro -- CONTENTS -- Acknowledgements -- About The Author -- Introduction -- Section 1: Appreciate What You've Got -- Lucky Name -- Lucky Place -- Lucky Legacy -- Lucky Feet -- Lucky Dude -- Lucky Mascot -- Lucky People -- Lucky Fuel -- Lucky Pack -- Lucky Timing -- Section 2: Look Out For Opportunities Everywhere -- Lucky George -- Lucky Leap -- Lucky Paint -- Lucky Dog -- Lucky Numbers -- Lucky Shrink -- Lucky Cakes -- Lucky Aliens -- Lucky Carrots -- Lucky Bags -- Section 3: Turn Misfortune Into Good Fortune -- Lucky Rabbit -- Lucky Coffin -- Lucky Escape -- Lucky Lockdown -- Lucky Hitch Lucky Limits -- Lucky Mice -- Lucky Bore -- Lucky Bastards -- Lucky Pencils -- Section 4: Practise Being Lucky -- Lucky Shot -- Lucky Goal -- Lucky Dip -- Lucky Trick -- Lucky Laces -- Lucky Lines -- Lucky Lord -- Lucky Charm -- Lucky Eggs -- Lucky You -- Conclusion -- References -- Publishing details.
Includes bibliographical references and index.
Keywords: BRANDING